NEW FINDINGS OF HELMINTHS PARASITES OF CHRYSOCYON BRACHYURUS (CARNIVORA: CANIDAE) IN ARGENTINA - González, Carlos A. (2013)
Canine parasitosis studies, in particular those of Chrysocyon brachyurus Illiger, 1815, are limited. Additionally, there are only few reports in the north of Argentina. The purpose of this study was to expand the knowledge about the helmith parasites of C. brachyurus. Necropsies of two adult specimens of C. brachyurus from two protected areas of Corrientes Argentina, were done in our laboratory. The biological material consisted of the viscera taken from a male canine found in the Mburucuya National Park and from a female found in the Rincon de Santa Maria Reserve. Centrorhynchus guira Lunaschi & Drago, 2010 and Ancylostoma caninum Ercolani, 1859 helminthes were found in the intestine, and Doctophyme renale Goeze, 1782 was found in the right kidney of the specimen coming from the Mburucuyá National Park. On the other hand, the specimen coming from the Rincon Santa Maria Reserve only presented with Mesocestoides sp Vaillant, 1863, in the small intestine. We here report for the first time, associations between C. guira - C. brachyurus and Mesocestoides sp. – C. brachyurus.